Infrastructure interdependencies: opportunities from complexity - Grafius, Darren R.; Varga, Liz; Jude, Simon (American Society of Civil Engineers (ASCE), 2020)
Infrastructure networks, such as those for energy, transportation, and telecommunications, perform key functions for society. Although such systems have largely been developed and managed in isolation, infrastructure now functions as a system of systems, exhibiting complex interdependencies that can leave critical functions vulnerable to cascade failure. Consequently, research efforts and management strategies have focused on risks and negative aspects of complexity. This paper explores how interdependencies can be seen positively, representing opportunities to increase organizational resilience and sustainability. A typology is presented for classifying positive interdependencies, drawing on fundamental principles in ecology and validated using case studies. Understanding opportunities that arise from interdependency will enable better understanding and management of infrastructure complexity, which in turn will allow the use of such complexity to the advantage of society. Integrative thinking is necessary not only for mitigating risk but also for identifying innovations to make systems and organizations more sustainable and resilient.
Keywords: complexity; infrastructure interdependency; resilience; sustainability; system-of-systems